2018
DOI: 10.1007/s00709-018-1216-2
|View full text |Cite
|
Sign up to set email alerts
|

Nectar trichome structure of aquatic bladderworts from the section Utricularia (Lentibulariaceae) with observation of flower visitors and pollinators

Abstract: In Utricularia, the flower spur is a nectary and in this organ, nectar is produced and stored. This study aimed to examine the structure of the nectary trichomes in four Utricularia species (Utricularia vulgaris L., U. australis R.Br., U. bremii Heer and U. foliosa L.) from the generic section Utricularia. We have investigated whether species with different spur morphology had similar spur anatomy and nectary trichome structure. In Utricularia flowers, nectar is produced by spur capitate trichomes (sessile or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 40 publications
5
18
0
Order By: Relevance
“…Our studies expand upon earlier descriptions of the morphology and ultrastructure of the cotton foliar nectaries (Eleftheriou and Hall, 1983a; Wergin et al, 1975), and extends such studies to the floral nectary and the reproductive extrafloral nectaries (i.e., bracteal and circumbracteal). The four nectaries of G. hirsutum share the basic structural components of similar trichomatic nectaries reported in other taxa ( Abutilon - Kronestedt et al, 1986; Hibiscus - Sawidis et al, 1987; Platanthera - Stpiczyńska et al, 2005; Utricularia - Plachno et al, 2018). Specifically, subnectariferous parenchyma is associated with vasculature.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our studies expand upon earlier descriptions of the morphology and ultrastructure of the cotton foliar nectaries (Eleftheriou and Hall, 1983a; Wergin et al, 1975), and extends such studies to the floral nectary and the reproductive extrafloral nectaries (i.e., bracteal and circumbracteal). The four nectaries of G. hirsutum share the basic structural components of similar trichomatic nectaries reported in other taxa ( Abutilon - Kronestedt et al, 1986; Hibiscus - Sawidis et al, 1987; Platanthera - Stpiczyńska et al, 2005; Utricularia - Plachno et al, 2018). Specifically, subnectariferous parenchyma is associated with vasculature.…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to the previous studies of foliar nectaries, cell wall ingrowths were observed during the secretory stage of bracteal and circumbracteal nectaries on the distal cell wall of the papillae head cells. These ingrowths in the region of nectar secretion, may facilitate nectar secretion by increasing the surface area (Fahn, 1979; Plachno et al, 2018), which may be particularly important for the reproductive extrafloral nectaries that produce the largest volume of nectar and are active for the duration of fruit maturation (Wäckers and Bonifay, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spur anatomy of the Pinguicula that were examined here is very similar to Utricularia (Płachno et al 2016(Płachno et al , 2017(Płachno et al , 2018(Płachno et al , 2019b. In both genera, there are collateral vascular bundles in the nectaries (spurs).…”
Section: Discussionmentioning
confidence: 83%
“…In Utricularia, the spur is treated as a nectary and nectar is produced by small glandular trichomes (Płachno et al 2017(Płachno et al , 2018(Płachno et al , 2019b. The ultrastructure of these trichomes was analysed by Płachno et al (2017Płachno et al ( , 2019c.…”
Section: Introductionmentioning
confidence: 99%